Board-gender diversity, family ownership, and dividend announcement: Evidence from Asian emerging economies - Adeel Mustafa; Abubakr Saeed; Muhammad Awais; Shahab Aziz (Journal of Risk and Financial Management, 2020)
In eras of intense debates on the appointment of women on corporate boards, this research sheds light on the structure of board in Asian emerging economies by examining how women on board of family businesses separately and collectively affect the dividend announcement of business organizations. On the basis of the panel data of four Asian emerging economies—China, Malaysia, Pakistan, and India—for the period 2010-2018, the results from our Tobit regression showed the adverse (negative) and significant impact of women on boards and in family businesses upon dividend announcement. It is important that policymakers should not view firms with one eye. There should be a spillover on board gender diversity from international to domestic levels, and international firms should be set as an example for domestic firms for the inclusion of women on boards. It might be the best time for Asian emerging economies to take productive action for balancing the gender in boardroom settings, and to set a minimum mass of women on boards for better and more effective decision making.
Keywords: 330; board gender-diversity; dividend announcement; emerging markets; family ownership